Метод расчета многослойных структур - Горячев Б. В. Борис Валентинович; Кутлин А. П.; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А. (Томск, 1985)
Деп. в ВИНИТИ 19.02.85, № 1295-85